Ammonia Oxidizing Prokaryotes Respond Differently to Fertilization and Termination Methods in Common Oat’s Rhizosphere - Allegrini, Marco; Morales, Marianela E.; Villamil, Maria B.; Zabaloy, María Celina (Frontiers in Microbiology, 2021)
Cover crops (CC) have demonstrated beneficial effects on several soil properties yet questions remain regarding their effects on soil microbial communities. Among them, ammonia-oxidizing bacteria (AOB) and archaea (AOA) have a key role for N cycling in soil and their responses in the rhizosphere of terminated CC deserve further investigation. A greenhouse experiment was established to assess N fertilization (with or without N) and termination methods (glyphosate, mowing, and untreated control) of common oat (Avena sativa L.) as potential drivers of AOA and AOB responses in the rhizosphere. The abundance of amoA genes was determined by quantitative Real Time PCR (qPCR), the community structure was assessed with Illumina amplicon sequencing of these genes, while the function was assessed from potential nitrification activity (PNA). While N fertilization had no influence on AOA, the termination method significantly increased amoA gene copies of AOA in mowed plants relative to glyphosate termination or the untreated control (1.76 and 1.49–fold change, respectively), and shifted AOA community structure (PERMANOVA, P < 0.05). Ordination methods indicated a separation between AOA communities from control and glyphosate-terminated plants relative to mowed plants for both UniFrac and Aitchison distance. Converserly, N fertilization significantly increased AOB abundance in the rhizosphere of mowed and control plants, yet not in glyphosate-treated plants. Analyses of community structure showed that AOB changed only in response to N fertilization and not to the termination method. In line with these results, significantly higher PNA values were measured in all fertilized samples, regardless of the termination methods. Overall, the result of this study indicated that bacterial and archaeal nitrifiers have contrasting responses to fertlization and plant termination methods. While AOA were responsive to the termination method, AOB were more sensitive to N additions, although the stimulative effect of N fertilization on amoAAOB abundance was dependent on the termination method.